Isolation and identification of coliform bacteria from spicy yogurt milk and plain butter milk sold in different markets of Dhaka city - Azam, Ariful (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2017.